PERSPEKTIF KEBIJAKAN PUBLIK TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 90/PUU-XXI/2023 SYARAT CALON WAKIL PRESIDEN PADA PEMILU 2024 - Fadilah, Ulvia; Hendrawati, Sulkiah; Saepudin, Eli Apud (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
Constitutional Court Decision Number 90/PUU-XXI/2023 is seen as a critical decision that is very debatable and controversial in the political view of public policy and goes beyond the authority of the Constitutional Court itself. The purpose of this study is to review the public policy perspective of the constitutional court's decision which is very interesting to review and examine. This research emphasizes the use of normative legal research, conceptual approaches, perceptions of public policy and this research method is qualitative analysis. The results of this study indicate that the Constitutional Court Decision Number 90/PUU-XXI/2023 must be constructed separately from the controversy that accompanied it and must be institutionalized constructively. The suggestion presented in this paper is the need for prior socialization of the public policy contained in the Constitutional Court Decision Number 90/PUU-XXI/2023